Seeing double : shared identities in physics, philosophy, and literature - Pesic, Peter (MIT Press, 2002)
"The separateness and connection of individuals is perhaps the central question of human life: What, exactly, is my individuality? To what degree is it unique? To what degree can it be shared, and how? To the many philosophical and literary speculations about these topics over time, modern science has added the curious twist of quantum theory, which requires that the elementary particles of which everything consists have no individuality at all. All aspects of chemistry depend on this lack of individuality, as do many branches of physics. From where, then, does our individuality come?" "In Seeing Double, Peter Pesic invites readers to explore this intriguing set of questions. He draws on literary and historical examples that open the mind (from Homer to Martin Guerre to Kafka), philosophical analyses that have helped to make our thinking and speech more precise, and scientific work that has enabled us to characterize the phenomena of nature. Though he does not try to be all-inclusive, Pesic presents a broad range of ideas, building toward a specific point of view: that the crux of modern quantum theory is its clash with our ordinary concept of individuality. This represents a departure from the usual understanding of quantum theory. Pesic argues that what is bizarre about quantum theory becomes more intelligible as we reconsider what we mean by individuality and identity in ordinary experience. In turn, quantum identity opens a new perspective on us."--Jacket